EFL Students’ Perceptions of Utilizing Podcasts towards Learning-Teaching Performance - Juhansar Juhansar; Nararya Rahadyan Budiono; Feby Yusalda; Safira Zahra Prasetya; Cintya Rima Puspitasari; Ari Prasetyoaji (Universitas Muhammadiyah Enrekang, 2022)
The development of technology contributes to the world of education, such as podcasts. It can be an alternative media for EFL students’ learning-teaching. This research aims to discover the EFL students’ learning-teaching performance through the podcast and explore their perceptions about the use of podcasts in learning-teaching performance. This research design is qualitative descriptive, and the respondents are the International Relations Department in semester three EFL students at the University of Technology Yogyakarta. The questionnaire was used in this study to collect the data. This research has two different questionnaires; the first contains the podcast material, and the second questionnaire contains questions about the perception of learning-teaching performance using podcasts. This research shows that EFL students’ learning-teaching performance using podcasts is good. It is proven by half of the respondents getting scores above the average, 63.82. Besides, EFL students agree that podcasts help their learning-teaching performance and give them new insight, such as new vocabulary. This research is limited to small-scale research, International Relations Department students in semester three. Thus, it is expected to conduct further wide-scale research related to the podcast.